Using consensus mapping methods as an efficient way of depicting avian distributions in the Caatinga Dry Forest, a poorly known Neotropical biome - Leandro-Silva, Victor; Silva, Marcos Vinicius Alexandre da; Pinto, Flávia Santos [UNESP]; Naka, Luciano Nicolás (Springer Nature, 2022)
Mapping species distributions has become central for biodiversity research. Different mapping methods, however, may result in dramatically different spatial patterns. We used expert-drawn maps (EDMs), minimum convex polygons (MCPs), ecological niche models (ENMs), and consensus models, to compare patterns of species ranges and species richness in 12 species of Psittacidae in a poorly known Neotropical ecosystem, the Caatinga Dry Forest. We validated results by comparing the ability of each method to predict the number of Psittacidae species in 17 localities with well-studied avifaunas. Size ranges were highly correlated (from 0.7 to 0.9) among mapping methods, but presented critical spatial differences, which resulted in very different patterns of species richness. When confronted with real data, MCPs and the EDM/MCP consensus method, both correctly predicted the presence of ~ 90% of the species present in the studied areas. However, when taking commission errors into account, MCPs presented the lowest efficiency (56%) among all methods. All three consensus methods (ENM/EDM, ENM/MCP, and EDM/MCP) performed better (> 74% efficiency) than any single method. We conclude that single mapping methods are prone to both higher omission and commission errors, and advocate for the use of consensus methods whenever species ranges will be used in macroecological studies.
Keywords: Caatinga; Mapping methods; Parrots; Species ranges; Species richness